Enhancing Purchase Intention through Service Quality: The Mediating Role of Customer Satisfaction and Competitive Advantage in Batam City Supermarkets - Budiman, Johny; Maridza, Fidella Dita (Dinasti Publisher, 2026)
This study aims to examine the influence of service quality on customer satisfaction, competitive advantage, and purchase intention among customers of five supermarkets in Batam City: Top 100, DC Supermarket, Hypermart, JC Supermarket, and SNL Food. A quantitative method was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on data collected from 306 respondents. The result indicates that service quality has a significant positive impact on customer satisfaction, competitive advantage, and purchase intention. Furthermore, competitive advantage significantly mediates the relationship between service quality and purchase intention, while customer satisfaction does not show a direct or mediating effect. These findings highlight the strategic importance of service quality in fostering sustainable competitive advantage, which has a stronger influence on consumers’ purchasing decisions than short-term satisfaction. Theoretically, this study contributes to the retail marketing literature. Practically, it provides valuable insights for retail managers to develop service strategies focused on long-term value creation and differentiation.